Constraints on the Cryohydrological Warming of Firn and Ice in Greenland From Rayleigh Wave Ellipticity Data - Jones, GA; Ferreira, AMG; Kulessa, B; Schimmel, M; Berbellini, A; Morelli, A (American Geophysical Union (AGU), 2023)
Rayleigh wave ellipticity measurements from seismic ambient noise recorded on the Greenland Ice Sheet (GrIS) show complex and anomalous behavior at wave periods sensitive to ice (T < 3–4 s). To understand these complex observations, we compare them with synthetic ellipticity measurements obtained from synthetic ambient noise computed for various seismic velocity and attenuation models, including surface wave overtone effects. We find that in dry snow conditions within the interior of the GrIS, to first order the anomalous ellipticity observations can be explained by ice models associated with the accumulation and densification of snow into firn. We also show that the distribution of ellipticity measurements is strongly sensitive to seismic attenuation and the thermal structure of the ice. Our results suggest that Rayleigh wave ellipticity is well suited for monitoring changes in firn properties and thermal composition of the Greenland and Antarctic ice sheets in a changing climate.